Building a distance learning network for management training of agricultural development managers in the Latin American and Caribbean Region - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2020)
The article explain the ISNAR and IICA jointly prepared a proposal to deliver agricultural research management training in 3 countries (Costa Rica, Dominican Republic and Honduras), as a pilot project. The lessons of the pilot project would be used to prepare the delivery of agricultural research management training to the entire LAC region.